ANÁLISIS SOBRE LA IMPORTANCIA DE LA SEGURIDAD Y SALUD EN EL TRABAJO EN EL SECTOR DE LA CONSTRUCCIÓN EN COLOMBIA - Carlos Alejandro Nuñez Arteaga (Revista Ingeniería, Matemáticas y Ciencias de la Información)
We are facing one of the economic sectors that annually reports the most occupational accidents to occupational riskmanagers in our country, the construction sector. Through a statistical analysis supported by figures provided by theFederation of Insurers of Colombia - Fasecolda, we argue the need for our country to place special emphasis on thesupervision of occupational health and safety in the construction sector, a sector that Despite presenting high mortalityrates, especially in unskilled labor, it fails to visualize a clear and responsible commitment on the part of employers, inthis case the construction companies and the regulatory body, which in the case of our country It has been the Ministry ofLabor when carrying out the implementation and subsequent monitoring of the activities aimed at safeguarding thephysical integrity of workers and operators, even though there are management strategies and regulations that supportsaid processes from a legal point of view.